Respuesta :

Answer:

SR =3

Step-by-step explanation:

SR + RQ = SQ

2x+23 + x+21 = 14

Combine like terms

3x+44 = 14

Subtract 44 from each side

3x+44-44= 14-44

3x = -30

Divide each side by 3

3x/3 = -30/3

x = -10

SR = 2x+23 = 2(-10)+23 = -20+3 =3

Answer: 3

Step-by-step explanation:

We can start by making an equation.

Since we know the total length of SQ we can add SR + RQ to equal SQ.

[tex](2x+23)+(x+21)=14[/tex]

The parenthesizes are not necessary but they help for understanding the parts of the equation.

We will remove the parenthesizes and combine like terms.

[tex]3x+44=14\\[/tex]

Now subtract 44 from both sides to cancel it out from the side with x.

[tex]3x=-30[/tex]

Now divide by 3 to isolate x.

[tex]x=-10[/tex]

So x = -10.

Now we can plug in the value of x into SR.

[tex]2(-10)+23 = SR[/tex]

Solve

So SR = 3

ACCESS MORE